Studies on the metabolic changes accompanying bacteriophage infection - Haslam, E (1967)
The infection of bacteria by viruses provides a simple system with which to study the basic processes of viral infection. Until about 1960 detailed bacteriophage research was restricted almost entirely to bacteriophages of Escherichis coli. Since 1960 a number of bacteriophages of Bacilius subtilis have been investigated. B. substilis was chosen as a suitable host organism because it will grow in a simple chemically-defined medium, because auxotrophic mutants may be isolated, and because such mutants may be genetically mapped by transformation. A group of virulent B. substilis phages which are of particular interest contain hydroxymethyluracil in place of thymine in their DNA. They are comparable with the extensively-investigated T-even coliphages which contain hydroxymethylcytosine in place of cytosine in their DNA. The presence of the unusual base provides a means of identifying phase DNA in the infected cell, and of studying the phage-induced alterations of metabolism necessary for the biosynthesis of the unusual nucleotide. The virulent phages of B. subtilis have therefore been further investigated. By analogy with the T-even coliphages the B. subtilis phages were expected to induce two special classes of enzymes after infection. These are (i) enzymes involved in the biosynthesis of hydroxymethyluracil, and (ii) enzymes which prevent the accumulation of thymidine triphosphate (dTTP) and its subsequent incorporation into phage DNA. The biosynthesis of hydroxymethyluracil is satisfactorily accounted for by the presence, in phage-infected cells, of an enzyme which hydroxymethylates enzyme which deamintes deoxycytidylic acid may augment the normal intracellular supply of dUMP and thus control the relative levels of phoshorylated derivatives of deoxycytidine and hydroxymethyldeoxyuridine. There is less general agreement about the phage-induced control of thymine biosynthesis. Different B. subtilis phages have been found to induce (i) an enzyme which hydrolyses dTTP to thymidylic acid (dTMP); (ii) an enzyme which hydrolyses dTTP to thymidine; and (iii) a rapid disappearance of the enzyme (thymidylate synthetase), which catalyses a methylation of dUMP to form dTMP. One of the aims of the present investigation was to determine whether one phage induced more than one of the possible mechanisms for preventing the incorporation of thymine into phage DNA. The second object of the work was to investigate the phage øe-induced inactivation of dTMP synthetase. The rapidity of the inhibition and the circumstances of its occurrence suggested the operation of an unusual form of control of enzyme activity. The control of metabolism by agents which inhibit existing enzymes is well-known in the case of feed-back inhibition, where a small molecular weight substance is implicated. The possibility that enzymes may be inactivated is a neglected aspect of metabolic control. A few examples of enzymes disappearing rapidly as a result of phage infection or as a result of the representation of enzyme synthesis are known and in some cases a protein inhibitor is implicated. The phage-induced inactivation of dTMP synthetase has also been shown to be caused by a protein inhibitor. The properties of the inhibitor and the mechanism of its interaction with dTMP synthetase. The inhibition of dTMP synthetase was detectable 5 min after the addition of phage øe and less than 10% of the original activity remained at 12 min after infection. If protein synthesis was inhibited no loss of dTMP synthetase occurred. An inhibitor of dTMP synthetase was detacted in extracts from phage-infected cells. It had the properties of a protein. It was heat-labile, non-dialysable, excluded from Sephadex G25, precipitated by ammonium sulphate and destroyed by digestion with trypsin. The amount of inhibitor present in extracts from phage-infected cells increased for at least the first 25 min of phage infection. It therefore behaved as if it were a phage-induced protein. In order to study the mechanism of the inhibition process, dTMP synthetase was purified 30 fold from uninfected B. substilis using ammonium sulphate fractionation, DEAE-cellulose chromatography and gel filtration. The inhibitor was purified 10-20 fold from B. substilis cells which were harvested 25 min after infection. The purification of the inhibitor involved ammonium sulphate fractionation and DEAE-cellulose chromatography, and was complicated by the instability of the inhibitor. The interaction of dTMP synthetase and the inhibitor was studied most thoroughly using their respective ammonium sulphate fractions. However preliminary results with the more highly purified samples of bith proteins tended to confirm the resultsobtained with the less pure system. In order to detect and assay the inhibitor it was necessary to preincubate it with a sample of dTMP synthetase at 37° for a short period of time (10 min usually) before assaying the mixture for residual dTMP synthetase activity. The interaction between the two proteins was not instantaneous. Thymidylate synthetase activity continued to decrease for at least 50 min after the addition of the inhibitor. the inhibition reaction was biphasic at both 25° and 37°. An initial fast reaction was followed by a slower linear one. The rate of the fast reaction was dependant on the temperature and pH of the incubation medium and on the concentrations of both the inhibitor and dTMP synthetase except when either was present in a presumed excess. The inhibitor acted directly on dTMP synthetase and was not an enzyme invalidating the essay for the latter. Two possible mechanisms for the action of the inhibitor were considered. It could either act catalytically, or it could act stoichiometrically to form a stable complex with dTMP synthetase. It was not possible to distinguish between these two mechanisms experimentally, the chief problems being the instability of the inhibitor and the absence of any means of identifying inhibited dTMP synthetase. Purification of the two proteins should eventually allow the mechanism of the interaction of dTMP synthetase and the inhibitor was analoguous to its effect on the interaction of the pancreatic trypsin inhibitor with trypsin, and a stoichiometric mechanism is perhaps more likely for this reason. The degree of inhibition of dTMP synthetase in vivo is unknown. It cannot be deduced from the activity found in cell-free extracts because when infected cells were sonicated at pH6 instead of at the usual level of pH of 7.5, the extracts contained uninhibited amounts of dTMP synthetase. Thus if the inhibitor functions in vivo the inhibition must be reversed by the violent conditions of celluler disruption, and the final activity of dTMP synthetase observed in cell-free extracts would then be due to a pH-dependent reassociation with the inhibitor. Although these observations also favour a reversible stoichiometric mechanism for the inhibition of dMTP synthetase, since the proposed inhibitor enzyme complex has not yet been dissociated in vitro, the possibility that the inhibitor and dTMP synthetase are brought together by cellular disruption cannot be excluded. The physiological role of the inhibtor. Assuming that the inhibition occurs in vivo, what is its physiological significance? Infection with phage SP8, which like phage øe contains hydroxymethyluracil in its DNA, was found to cause some inhibition of dTMP synthetase, although it was less effective in this respect than phage øe. Since phage SP8 induced a dTTPase the possibility that phage øe;e did ikewise was investigated by studying the multiplication of phage &oslah;e in a thymine-requiring host strain supplied with exogeneous thymidine. Multiplication was normal and no thymidine was incorporated into phage DNA. Since in this host the absence of dTMP sythetase is bypassed by the obligatory external supply of thymidine, the result implied that phage øe induced a second block in thymine biosynthetsin. The induction of a dTTPase by phage øe was confirmed by Dr. Roscoe. In view of these results, what is the reason for the inhibition of dTMP synthetase during phage infection? In spite of the presence of a dTTPase the inhibition of dTMP synthetase could have a marginal role. Thymidylate synthetase is believed to be the main mechanism of thymine biosynthesis in B. subtilis although it is not the only source of dTMP. Its inhibitation during phage infection would prevent the wasteful removal of dUMP, which is utilised by the dUMP hydroxymethylase for the biosynthesis of hydroxymethyluracil. In addition, the product of the action of both dTMP synthetase and the phage-infected cell where it has no known role and in which it may even be inhibitory. Conclusion This work has provided an intersting example of the inhibition of an enzyme by a protein in circumstances which suggest that the inhibition could play a role in ensuring succesful viral infection. The inhibition may be one of an increasing number of examples in which the inactivation of an enzyme by a protein inhibitor is provoked by a sudden change in the metabolic balance of a cell.